THE EFFECT OF MOTIVATION, WORK DISCIPLINE AND WORK ENVIRONMENT ON THE WORK ACHIEVEMENT OF TEACHERS OF STATE VOCATIONAL SCHOOL - Euis Dwi Rosaeni; Ellin Herlina; Weti Kurniawati (PT. Berkah Digital Teknologi, 2022)
Purpose of the study — This study aims to determine and analyze the effect of Motivation, Work Discipline and Work Environment on the Work Achievement of Teachers at SMK Negeri 1 Cirebon, either partially or simultaneouslyResearch method— This study uses a quantitative approach. Quantitative approach, survey method, this type of research is causal associative research with data analysis technique using Multiple Linear Regression analysis. The population in this study were teachers of the State 1 Cirebon Vocational High School (SMK), Cirebon City as many as 105 people, a sample of 60 peopleResult— The results of this study indicate: 1) Motivation partially has a positive and significant effect on the work performance of teachers at SMK Negeri 1 Cirebon. The magnitude of the positive influence of motivation on work performance is 61.6%. 2) Work discipline partially has a positive and significant effect on the work performance of teachers at SMK Negeri 1 Cirebon. The magnitude of the influence of Work Discipline on Teacher Work Achievement is 25.5%. 3) The work environment partially has a positive and significant effect on the work performance of teachers at SMK Negeri 1 Cirebon. The magnitude of the influence of the work environment on teacher work performance is 21.8%. 4) Motivation, work discipline and work environment together have a positive and significant effect on the work performance of teachers at SMK Negeri 1 Cirebon. The magnitude of the influence of motivation, work discipline, work environment simultaneously on teacher work performance is 94.8%.Conclusion— The study found that motivation, work discipline, and work environment all have a positive and significant effect on the work performance of teachers. The combined influence of these factors is 94.8%. Practical Implications: The study suggests that increasing motivation, promoting work discipline, and improving the work environment can lead to improved work performance for teachers. Social Implications: The study highlights the importance of providing positive working conditions for teachers, which can have a positive impact on the education of students. Improving the work performance of teachers can lead to better education outcomes for students in the long run.